Fast thermo-optic switching through parity-time symmetry breaking - Pradip, Ravi; Varri, Akhil; McRae, Liam; Brückerhoff-Plückelmann, Frank; Wendland, Daniel; Lohmann, Philipp; Xu, Rongyang; Ovvyan, Anna; Taheriniya, Shabnam; Pernice, Wolfram; Ferrari, Simone (Optics express, 2025)
Reconfigurable photonic integrated circuits (PICs) are key elements for emerging applications like photonic sensing, LiDAR, and quantum computing. In such applications, optical switches with fast response and robust fabrication methods are crucial for reprogramming linear optical transformations on demand. Here, we demonstrate a fast thermo-optic switching mechanism on the silicon nitride on insulator platform, leveraging parity-time symmetry breaking. The cladding-free design operating at 775 nm enables optical propagation in a partially metal-covered waveguide with minimal loss—an uncommon phenomenon given the typical absorption associated with metal proximity. The fabricated device exhibits a 7.1 µs rise time for a π phase shift, despite the weak thermo-optic coefficient in silicon nitride. Our design provides reproducible fabrication metrics and holds promises for large-scale photonic networks operating at visible wavelengths.
Gesehen am 15.01.2026